PENERAPAN METODE MIND MAPPING DALAM MEMPRODUKSI TEKS PROSEDUR DI SMP - Evi Damayanti; Ida Puspa Kania; Cucu Kartini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research was motivated by the curiosity of the researchers regarding the effectiveness of using the Mind Mapping method in the learning process of producing procedure texts in class VII. This study aims to determine the production results of the procedure text of class VII students of Cimahi Middle School Kartika XIX-3 using the Mind Mapping method. The method used in this study is the experimental method. The study sample was class VII A SMP Kartika XIX-3 Cimahi with a total of 25 students. The technique of collecting data using the initial test (pre-test) and the final test (post-test). The instrument in this study was to use the initial test sheet (pre-test) and the final test (post-test). Based on the results of the research students' ability to produce text procedures before using the mind mapping method obtained an average value of the initial test (pre-test) amounted to 50.36 and after using the mind mapping method obtained the final test score (post-test) amounted to 77.68. The results of the ability to produce procedural texts increased by 27.32. So, it can be concluded that in applying the mind mapping method to learning producing procedural texts in class VII students can improve student learning outcomes.